Modelling the impact of dredging inlets on the salinity and temperature regimes in coastal lagoons. (1st October 2019) - García-Oliva, Miriam; Marcos, Concepción; Umgiesser, Georg; McKiver, William; Ghezzo, Michol; De Pascalis, Francesca; Pérez-Ruzafa, Angel
Abstract: Coastal lagoons support intense human activity. Dredging or closing the inlets to regulate water exchanges in order to manage fisheries or improve navigation, prevent floods, reduce pollution or prevent dystrophic crises are among the most frequent management actions. Increased social concerns about the Mar Menor have arisen during the last decades due to the speed and magnitude of changes in its water conditions, including eutrophication and the siltation of some of the channels connecting it to the Mediterranean. In response, the idea of opening the inlets in order to increase water exchange and renovation in the lagoon has gradually convinced managers and the public as being a potential solution. However, changing the morphology of the inlets does not only involve reducing or diluting nutrients or pollutants or facilitate fish movements, but may also affect the physical-chemical parameters governing the ecosystem, as temperature, that regulates metabolic activity and physiological performance of individuals and hence the biogeographical limits in the distribution of species, or salinity that is considered the key factor that determines species composition in brackish waters. In this framework, using a 3D model, we analyse the effect of different scenarios of dredging (up to 1.5 m more than the present depth of the two shallower inlets) on the spatio-temporal patterns in salinity and temperature in the Mar Menor coastal lagoon. We also check the ability of a geomorphological index (the openness parameter) to predict the observed changes. The magnitude and spatial extent of the impacts are proportional to the magnitude of the dredging activities, but they also depend on the season of the year and on the location of the dredged channels in relation to the main circulatory paths. On average, the salinity ratio can decrease by up to 3.45% with respect to the undisturbed scenario in the most extensive dredging simulation and the yearly average temperature can increase by up to 8.24% in the case of simple maintenance activities. All scenarios show a trend towards a smoothing out of extreme values in environmental conditions and the loss of spatio-temporal heterogeneity at basin scale. Even the most moderate actions can be of biological relevance at a local scale, and may have consequences for the whole lagoon affecting the possibilities of colonization or reproduction by some species and the ecosystem homeostatic regulation capacity. The openness parameter is seen to act as a good indicator of potential impacts of geomorphological alterations of the channels on lagoon salinity and temperature. Coastal lagoons are complex biological systems, and this kind of measure has to be suitably assessed in terms of the induced gain or loss for the functioning of the entire ecosystem. Highlights: Dredging the lagoon inlets decreases the salinity and softens the temperature range. The spatial homogenization and the softening of temporal variability are key effects The maximum salinity reduction happens during the fall. Temperatures decrease during spring-summer and increase in the fall-winter period. The openness parameter can be used as a quick indicator of impacts of dredging.